WHY ORGANIZATIONAL CITIZENSHIP BEHAVIOR IS IMPORTANT IN THE ERA OF INDUSTRY 4.0: A BIBLIOMETRIC ANALYSIS - Hakim A.R.; Febriani R. (Russian Journal of Agricultural and Socio-Economic Sciences)
Organizational Citizenship Behavior (OCB) is an essential aspect of organizational functioning, especially in the era of the Industrial Revolution 4.0. OCB behavior is a type of behavior that encourages the development of a positive work environment. This study uses Scopus and Scholar journal articles to conduct a bibliometric analysis of the antecedents and impacts of OCB in Indonesia; 789 documents were selected from 2019-2023 that have gone through manuscript selection. Bibliometric analysis with VOSViewer has explored the relationship between keywords, factors/antecedents of OCB behavior, and the impact of OCB behavior itself. The results of the Co-Occurance analysis showed that there were at least 46 antecedent items/factors that influenced OCB behavior. Items such as organizational commitment, motivation, perceived organizational support, organizational justice, organizational culture, transformational leadership, and job satisfaction were found to be widely researched and influenced by OCB. Meanwhile, the analysis found that OCB behavior has a significant influence and impact on at least 15 items, mainly on the variables of (1) employee performance, (2) job satisfaction, and (3) turnover intention, especially found a significant impact on employee performance. These findings underline that OCB behaviors are highly consistent with the organization's success, as proven by existing research. Organizations must maintain and enhance OCB behavior by establishing a positive and supportive work environment and culture that considers the factors influencing OCB.